Obesity a predictor of outcomes of COVID‐19 hospitalized patients—A systematic review and meta‐analysis. Issue 2 (7th October 2020) - Malik, Preeti; Patel, Urvish; Patel, Karan; Martin, Mehwish; Shah, Chail; Mehta, Deep; Malik, Faizan Ahmad; Sharma, Ashish
Abstract: Coronavirus disease 2019 (COVID‐19) pandemic is a global health crisis. Very few studies have reported association between obesity and severity of COVID‐19. In this meta‐analysis, we assessed the association of obesity and outcomes in COVID‐19 hospitalized patients. Data from observational studies describing the obesity or body mass index and outcomes of COVID‐19 hospitalized patients from December 1, 2019, to August 15, 2020, was extracted following PRISMA guidelines with a consensus of two independent reviewers. Adverse outcomes defined as intensive care units, oxygen saturation less than 90%, invasive mechanical ventilation, severe disease, and in‐hospital mortality. The odds ratio (OR) and 95% confidence interval (95% CI) were obtained and forest plots were created using random‐effects models. A total of 10 studies with 10, 233 confirmed COVID‐19 patients were included. The overall prevalence of obesity in our study was 33.9% (3473/10, 233). In meta‐analysis, COVID‐19 patient with obesity had higher odds of poor outcomes compared with better outcomes with a pooled OR of 1.88 (95% CI: 1.25–2.80; p = 0.002), with 86% heterogeneity between studies ( p < 0.00001). Our study suggests a significant association between obesity and COVID‐19 severity and poor outcomes. Our results findings may have important suggestions for the clinical management and future research of obesity and COVID‐19.